PENYULUHAN PERMODALAN BAGI USAHA MIKRO - Mahrus Ali (Asian Journal of Innovation and Entrepreneurship, 2013)
The main problem facing the majority of respondents is the lack of capital andmarketing difficulties. Although many special credit schemes for small enterprises, themajority of respondents, especially those located in rural areas, never get credit frombanks or other institutions. Implementation of extension activities to capital for micro-enterprises because lack of knowledge about the capital so that the business communitycan not thrive. Capital program for micro businesses helpful to develop a businessSungapan II Dusun community and foster new innovations in business. The stages of theactivities carried out during ongoing counseling is the identification, dissemination capital,capital counseling, debriefing. The result of this program is that people know what theexisting capital base and to understand where and how to obtain them.